2018
DOI: 10.1016/j.physletb.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the hydrodynamical combustion to strange quark matter in the trapped neutrino regime

Abstract: We simulate and study the microphysics of combustion (flame burning) of two flavored quark matter (u, d) to three flavoured quark matter (u,d,s) in a trapped neutrino regime applicable to conditions prevailing in a hot proto-neutron star. The reaction-diffusion-advection equations for (u,d) to (u,d,s) combustion are coupled with neutrino transport, which is modelled through a flux-limited diffusion scheme. The flame speed is proportional to initial lepton fraction because of the release of electron chemica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The formation of a strange star would certainly be accompanied by a release of energy, as discussed in framework of supernova explosions, see for example [26][27][28], possibly affecting the gamma and neutrino emissions associated to the merging of NSs. The GW post merger emission could also be different, but we are not aware of any simulation of merging of NSs leading to the formation of a strange star.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a strange star would certainly be accompanied by a release of energy, as discussed in framework of supernova explosions, see for example [26][27][28], possibly affecting the gamma and neutrino emissions associated to the merging of NSs. The GW post merger emission could also be different, but we are not aware of any simulation of merging of NSs leading to the formation of a strange star.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they found, by solving the semi-analytic, hydrodynamic jump conditions, that, for a given neutrino cooling rate, thermal pressure gradients could slow down the combustion front by orders of magnitude. Ouyed et al [17] (hereby Paper II) later confirmed this initial intuition numerically, by incorporating neutrino transport and electron pressure into the reaction-diffusionadvection equations. The authors of Paper II discovered that feedback effects triggered by various leptonic processes could affect the burning timescale by orders of magnitude.…”
Section: Introductionmentioning
confidence: 81%
“…Later on, Ouyed et al [18] explored the effect of neutrinos in the interface by implementing a neutrino diffusion scheme and including neutrinos and electrons in the EOS. They found that indeed, neutrinos can cause the interface to halt.…”
Section: Second Wave Studiesmentioning
confidence: 99%
“…In other words, including the dynamical effects of the reaction zone can lead to counter-intuitive behavior such as quenching due to time-dependent effects, which are not captured when using the steady state solutions of Olinto or the jump-conditions [18,17].…”
Section: Second Wave Studiesmentioning
confidence: 99%
See 1 more Smart Citation